PENERAPAN MODEL KOOPERATIF TIPE TWO STAY TWO STRAY (TSTS) UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS III SDN 005 RANTAU PANJANG KIRI KEC.KUBU BABUSSALAM KAB.ROKAN HILIR - Rasniwati, Rasniwati; Daud, Damanhuri; Munjiatun, Munjiatun (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract : Science learning in class III SDN 005 Rantau Panjang Kiri is low an average grade 63,96 this is caused by the learning is done by texs oriented book, wearing a lecture (conventional) and exercises with student involvement was minimal and many students are passive while learning. This research aims to improve learning outcomes 005 Grade III SDN Rantau Panjang Kiri Academic Year 2014/2015 through "Application of Cooperative Learning Model Two Stay Two Stray (TSTS)". This research was conducted in March 2015. The subjects were 005 third grade students of SDN Rantau Panjang Kiri numbering 24 people, consisting of 13 men and 11 women. This study was conducted in two cycles. Data collection instruments in this research is to test daily tests, observation of student activity sheets and sheets of observations of teacher activity. The average value of student learning outcomes has increased which before action 63.96, an increase in UH I became 77.50 and increased again at UH II became 86.67. Improvement of basic scores first cycle to 13.54 with the percentage of 21.17% enhacement and improvement of basic Scores Cycle II amounted to 22.71 with the percentage increase of 35.50%. Mastery learning students are also experiencing increasing 45.83% where as before action with incomplete categories increased in the first cycle of 75.00% with no complete category increased again in the second cycle of 91.67% with a complete category. The activities of teachers and students during the learning process also increased. Activity Cycle I teachers with an average of 70.00% categorized Enough, increased in the second cycle with an average of 85.00% categorized as good. Activity of students in the first cycle an average of 72.50% with enough categories increased in the second cycle average of 87.50% with the good category. it can be concluded that with the implementation of cooperative learning model type Two Stay Two Stray (TSTS) can improve learning outcomes IPA Class III SDN 005 Rantau Panjang Kiri Kubu Babussalam Districts Rokan Hilir Regency. Keyword: Cooperative Learning Model Two Stay Two Stray (TSTS), Learning Outcomes